Enhancing citizen capacity through optimising Village-Owned Enterprises (BUMDes) role in strengthening community participation for sustainable development - Supandi, Supandi; Saliman, Saliman (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
Sustainable development at the local level necessitates active community participation, bolstered by educational innovation and the optimisation of empowering institutions such as Village-Owned Enterprises (BUMDes). This research investigates the impact of the Social Studies Outdoor Laboratory and BUMDes on development in the Bokoharjo, Prambanan, Sleman Regency. Specifically, the study examines three key areas: (1) the influence of the Social Studies Outdoor Laboratory on development, (2) the role of BUMDes in facilitating development, and (3) the collaborative effect between the Social Studies Outdoor Laboratory and BUMDes on regional growth. A quantitative approach was employed, sampling nine individuals from Bokoharjo Village from September to October. Data collection involved questionnaires, while data analysis was conducted using multiple linear regression tests, with the instrument's validity assessed through the product-moment method. The results reveal that: (1) the Social Studies Outdoor Laboratory has a significant influence on enhancing development, with a significance value of 0.000; (2) BUMDes plays a crucial role in contributing to development, also with a significance value of 0.000; and (3) the combination of the Social Studies Outdoor Laboratory and BUMDes demonstrates a significant influence on development, with a p-value of 0.000. These findings underscore the importance of synergetic educational innovation and local community empowerment in promoting sustainable development.